PENGATURAN IZIN BEKERJA TERHADAP WARGA NEGARA ASING DI INDONESIA - Ida Bagus Gede Wahyu Boga Garbayana (Kerta Dyatmika, 2019)
Abstract The writer found that the legal facts that occurred in this study were related to the permission of foreigners to work in Indonesian namely, the clash of legal norms between the Immigration Act and the Manpower Act.The problem raised in this thesis is that how is the permits regulation for foreign workers to work in Indonesia and what are the forms of foreign workers permit procedures to work in Indonesia. The type of research is normative legal research, which departs from the existence of a conflict of legal norms between Law Number 6 of 2011 and Law Number 13 of 2003 concerning Manpower related to work permits regulation of foreigners in Indonesian. This study uses a regulatory approach and a legal concept analysis approach.The conclusion of this study is the work permits regulations of foreigners in Indonesian based on Law Number 6 of 2011 concerning Immigration by referring to the application of the principle of preference. The permit procedure for foreign workers to work in Indonesia is obtaining permission to employ foreign workers in Indonesia, first by submitting an RPTKA or Foreign Manpower Utilization Plan made by the employer such as filling identity and uploading the work agreement in accordance with applicable regulations, then the application will be submitted to the Director General or Director through online foreign workers. Keywords: Work Permit, Foreign Workers, Foreign Workers Permit Procedure